Methodological Contributions to Hadith Criticism Studies at UIN Alauddin Makassar: An Initial Reading - Aliah, Mujadid Sigit (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2024)
This article is motivated by the development of hadith studies in the contemporary period has experienced a very rapid development, one of which is the study of hadith at PTAI including UIN Alauddin Makassar which has been known as one of the PTAIs that has great attention to hadith especially because of the great name of M. Syuhudi Ismail and the development of the generation after him. This research aims to provide an initial reading of the methodological contribution of hadith studies at UIN Alauddin Makassar, so the main problem studied in this paper is how the discourse of hadith criticism methodology at UIN Alauddin Makassar for both sanad and matan. This study is qualitative library research that uses academic works at UIN Alauddin Makassar as its main source. This article shows that the contribution of the study of hadith criticism methodology has developed and contributed to all elements in the rules of hadith validity both on the sanad and on the matan, with a paradigm tendency towards a balance between the study of sanad and matan which can be distinguished but cannot be separated.